SENGKETA PULAU DOKDO (PULAU TAKESHIMA) ANTARA JEPANG DENGAN KOREA SELATAN DALAM PERSPEKTIF HUKUM INTERNASIONAL - Kadek Sri Indriyani (Jurnal Locus Delicti, 2022)
A country's territory is inextricably linked to its existence . Japan and South Korea relations have long been strained, and they have recently deteriorated, causing alarm among the international community, particularly in East Asia. Territorial disputes are a challenging matter to address. From a simple mutual claim of possession, it might quickly escalate into a conflict, resulting in strained relations between the countries concerned, and even leading to war. The Dokdo Island dispute between Japan and South Korea, also known as Takeshima Island, has lasted since 1905 and has yet to be settled. South Korea argues that the island of Dokdo is its’s geographically, according to international law, and historically. Meanwhile, Japan has stated and claimed ownership of the Takeshima (Dokdo) island. The study approach was normative juridical analysis, and the goal of this work was to investigate the Dokdo Island conflict (Takeshima Island) between Japan and South Korea from the standpoint of international law.